La lectura y su incidencia en el aprendizaje, en los estudiantes de segundo y tercer años de bachillerato general unificado, sección nocturna, de la unidad educativa Calasanz, de la ciudad de Loja, durante el año lectivo 2012–2013 - Cabrera Malla, Sandra Elizabeth (2015)
The research entitled: “READING AND ITS IMPACT ON LEARNING IN THE STUDENTS OF SECOND AND THIRD YEARS OF GENERAL BACHELOR UNIFIED , NIGHT SECTION,” THE UNIT EDUCATIONAL CALASANZ" IN LOJA CITY, DURING ACADEMIC YEAR 2012-2013”, was formulated as general objective "Determining the degree of incidence of reading in the development of learning of the students of second and third years of Bachelor General Unified, night section of the “Unit Educational Calasanz "in Loja city, during the academic year 2012-2013. Therefore, used the following methods: scientific, inductive, deductive, analytical and synthetic method; the techniques such as bibliography and the survey and an instrument (questionnaire). Among the main results be identified that the teachers of language and literature to develop skills apply the reading, but the lack of application of various methods and techniques of reading is contributing to low development of skills in the students. Thus, it concludes saying that the teachers in the Unit Educational Calasanz, apply reading improperly in its didactic, to permitted develop limited two basic skills in the students such as memorization and observation during all its period of transition at the school, for which were recommended to the teachers enhance the reading with the use of various methods, techniques, procedures and dynamics that call the attention of the students and with this achieve better learning.